Antiproliferative Effect of Ethanolic Extract Eugenia uniflora Lam. Leaves on T47D Cells - Nur Ismiyati; Dyaningtyas Dewi Pamungkas Putri; Siska Andrina Kusumastuti; Rifki Febriansyah (Indonesian Society for Cancer Chemoprevention, 2012)
Eugenia uniflora Lam. is one of herbal products developed for anticancer. The aim of the present study was to identify the antiproliferative effect of ethanolic extract of Eugenia Uniflora Lam. leaves (EEU) on breast cancer cell line T47D. This Research was initiated by extracting the active contents of Eugenia uniflora Lam. leaves by maceration with ethanol 96%. The extract was then analyzed by thin layer chromatography (TLC). Cytotoxic assay of EEU was carried out by using MTT assay. Apoptosis phenomenon was observed with double staining using acridine orange-ethidium bromide. EEU showed cytotoxic effect on T47D cells with IC50 value of 65 µg/ml. Moreover, EEU 50µg/ml and 100µg/ml induced apoptosis. TLC examination showed that EEU used in this study contain phenolic, flavonoid, and saponin compounds which were suggested to be responsible for antiproliferative effect. Further molecular mechanism underlying EEU antiproliferative effect needs to be done.Keywords: Eugenia uniflora Lam., T47D cells, antiproliferative, apoptosis